Leucine-Rich Glioma Inactivated 1 Promotes Oligodendrocyte Differentiation and Myelination via TSC-mTOR Signaling - Xie, Ya-Jun (Front Mol Neurosci, 2018)
Leucine-rich glioma inactivated 1 (Lgi1), a putative tumor suppressor, is tightly associated with autosomal dominant lateral temporal lobe epilepsy (ADLTE). It has been shown that Lgi1 regulates the myelination of Schwann cells in the peripheral nervous system (PNS). However, the function and underlying mechanisms for Lgi1 regulation of oligodendrocyte differentiation and myelination in the central nervous system (CNS) remain elusive. In addition, whether Lgi1 is required for myelin maintenance is unknown. Here, we show that Lgi1 is necessary and sufficient for the differentiation of oligodendrocyte precursor cells and is also required for the maintenance of myelinated fibers. The hypomyelination in Lgi1(−/−) mice attributes to the inhibition of the biosynthesis of lipids and proteins in oligodendrocytes (OLs). Moreover, we found that Lgi1 deficiency leads to a decrease in expression of tuberous sclerosis complex 1 (TSC1) and activates mammalian target of rapamycin signaling. Together, the present work establishes that Lgi1 is a regulator of oligodendrocyte development and myelination in CNS.